Left Ventricular Ejection Fraction 1 Year After Acute Myocardial Infarction Identifies the Benefits of the Long-Term Use of β-Blockers: Analysis of Data From the KAMIR-NIH Registry. (April 2021) - Park, Chan Soon; Yang, Han-Mo; Ki, You-Jeong; Kang, Jeehoon; Han, Jung-Kyu; Park, Kyung Woo; Kang, Hyun-Jae; Koo, Bon-Kwon; Kim, Chong-Jin; Cho, Myeong Chan; Kim, Young Jo; Chae, Shung-Chull; et al.
Abstract : Background: β-Blockers can improve prognosis after acute myocardial infarction. However, it remains unclear how long β-blockers should be prescribed. Methods: We included patients from the prospective, nationwide Korea Acute Myocardial Infarction Registry-National Institutes of Health registry and collected data on β-blockers and left ventricular ejection fraction (LVEF) at 1-year follow-up. Patients were stratified into 2 groups: 1001 patients with a 1-year LVEF<50% and 3007 patients with a 1-year LVEF≥50%. The primary outcome was 2-year all-cause mortality from the 1-year follow-up. Results: A total of 3177 patients received β-blockers at 1 year, and 151 patients died during the 2-year follow-up from 1 year after index hospitalization. β-Blockers showed survival benefits in patients with a 1-year LVEF<50% (log-rank P =0.001) but not in those with a 1-year LVEF≥50% (log-rank P =0.311). After adjusting covariates, β-blockers were associated with a 51% reduction in mortality in patients with a 1-year LVEF<50% ( P =0.020) but not in their counterparts ( P =0.322). Indeed, there was a prognostic interaction between the use of β-blockers at 1 year and 1-year LVEF ( P for interaction=0.004). Conclusions: Use of β-blockers at 1-year follow-up after acute MI was associated with improved outcomes in patients with an LVEF<50% at 1 year but not in those with an LVEF>50% at 1 year. This study provides valuable information about differential responsiveness to β-blockers according to 1-year LVEF and might suggest the proper duration of β-blockers after acute MI. Registration: URL: http://cris.nih.go.kr/cris/en/ ; Unique identifier: KCT0000863. Abstract : Supplemental Digital Content is available in the text.